2021
DOI: 10.1109/jlt.2021.3057804
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Scramblers to Solve Practical Limitations of Frequency Transfer

Abstract: Polarization variations in optical fibers are complex and would severely affect the performances of polarizationsensitive signal distribution systems. Owing to advances in experimental techniques and theoretical tools, we observe the effect of polarization variations in the optical fibers and we demonstrate that polarization mode dispersion (PMD) dominates the free-running fiber noise. Ultrahigh correlation, over 99%, is found between the phase fluctuation induced by polarization variation and the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This could be due to some technical limitations, such as for instance non-optimal parametrization of the SoftPLL and/or the WR engine, mistakes in the phase comparator (that is to say the digital dual mixer time difference meter implemented in the FPGA at heart of the WR engine [67]), or mistakes in the servo loop physical model. It could also be due to an asymmetry in the propagation delay for the forward and backward signal that were not well taken into account in our model, possibly linked to more fundamental reasons such as the effect of temperature on birefringence of the fiber as reported recently in the optical domain with fiber spools [68], [69].…”
Section: Discussionmentioning
confidence: 93%
“…This could be due to some technical limitations, such as for instance non-optimal parametrization of the SoftPLL and/or the WR engine, mistakes in the phase comparator (that is to say the digital dual mixer time difference meter implemented in the FPGA at heart of the WR engine [67]), or mistakes in the servo loop physical model. It could also be due to an asymmetry in the propagation delay for the forward and backward signal that were not well taken into account in our model, possibly linked to more fundamental reasons such as the effect of temperature on birefringence of the fiber as reported recently in the optical domain with fiber spools [68], [69].…”
Section: Discussionmentioning
confidence: 93%
“…However, such a solution cannot work reliably in practice, as standard fibers change their polarization state randomly due to external factors such as temperature and mechanical stress variations [16]. A simple solution may be to use a polarization scrambler [16], [32], which is a standalone fiber-optic component, not requiring any additional feedback loop or control algorithms (in contrast to an adaptive polarization controller). However, the polarization scrambler reduces the average power of the beat by 3 dB, resulting in a modulation of the IF signal level driving the prescaler (see Fig.…”
Section: Penalty Due To Polarization Scramblingmentioning
confidence: 99%
“…However, asymmetric transmission spectrum of FRR has been observed in many researches, results in the inability of the laser center frequency to track and lock the resonant frequency of the FRR, thereby seriously affecting system stability [9]. Prior studies have indicated that including polarization fluctuation [10], Kerr effect [11], temperature disturbance [12], and coupler manufacturing error [13]will affect the symmetry of the resonance curve, of which coupler error is the most influential. Classic theoretical model simply define the orthogonal mode loss difference of the coupler as π/2, therefore, it can not This work was supported in part by the National Natural Science Foundation of China under grant 52075131.…”
Section: Introductionmentioning
confidence: 99%